2013
DOI: 10.1039/c3mt20213e
|View full text |Cite
|
Sign up to set email alerts
|

Selenium mediated arsenic toxicity modifies cytotoxicity, reactive oxygen species and phosphorylated proteins

Abstract: The effect of selenium on modulating arsenic cytotoxicity is well known in mammals, but not well understood. Cell cytotoxicity and reactive oxygen species (ROS) changes were performed in combinations of As(III) and selenomethionine (SeMet) toxic mixes on, HEK293, human kidney cells. Cell growth is readily restored from 20% to 60% when switching from 30 μM As(III) as toxin to a mix of 30 μM As(III) and 100 μM SeMet. As(III) alone triggers ROS formation, primarily hydrogen peroxide, in a concentration dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 82 publications
(110 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, our results showed that selenomethionine blocked OTA-induced ROS production and GSH depletion in PK15 cells in a dose-dependent manner. These results are consistent with that of a previous study, which found that selenomethionine treatment lowered the total amount of ROS generated by As (III) treatment in HEK293 human kidney cells [ 47 ]. Together, the present results strongly suggested that selenomethionine protected PK15 cells against OTA-induced cytotoxicity and apoptosis by improving cellular antioxidant capacity.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our results showed that selenomethionine blocked OTA-induced ROS production and GSH depletion in PK15 cells in a dose-dependent manner. These results are consistent with that of a previous study, which found that selenomethionine treatment lowered the total amount of ROS generated by As (III) treatment in HEK293 human kidney cells [ 47 ]. Together, the present results strongly suggested that selenomethionine protected PK15 cells against OTA-induced cytotoxicity and apoptosis by improving cellular antioxidant capacity.…”
Section: Discussionsupporting
confidence: 93%
“…Using the comet assay, the researchers also found that nanoSe prevented arsenite-dependent DNA damage [99]. In another in vitro study, an organic Se form (SeMet, 100 μM) protected human kidney cells from arsenite (30 μM)-induced cell cytotoxicity and ROS generation [98]. Inorganic Se administered as selenite (10 μΜ) induced antioxidant, antiautophagic, and antiapoptotic effects in arsenite (10 μΜ)-treated PC12 cells [100].…”
Section: Use Of Se In the Prevention Of As Intoxication In Animal Andmentioning
confidence: 99%
“…The antagonistic effect of Se on arsenic toxicity has been gradually accepted by the public. In recent years, in vitro research showed that Se can alleviate arsenic toxicity by modifying cytotoxicity, genotoxicity and oxidative stress [46,47]. This is confirmed by a study carried out by Sah and Smits (2012), who suggested dietary Se at 0.6 mg/ kg, improved the antioxidant capacity and counteracted chronic as toxicity in rats [48].…”
Section: Discussionmentioning
confidence: 77%